First Nations Peoples' Participation in the Development of Population-Wide Food and Nutrition Policy in Australia: A Political Economy and Cultural Safety Analysis - Jennifer Browne; Michelle Gilmore; Mark Lock; Kathryn Backholer (Kerman University of Medical Sciences, 2021)
BackgroundHealthy and sustainable food systems underpin the well-being of Indigenous peoples. Increasingly governments are taking action to improve diets via population-wide policies. The United Nations Declaration on the Rights of Indigenous People states that Indigenous peoples have the right to participate in all decisions that affect them. We analysed Australian national food and nutrition policy processes to determine: (i) the participation of Aboriginal organisations, (ii) the issues raised in Aboriginal organisations' policy submissions, and (iii) the extent to which Aboriginal organisations' recommendations were addressed in final policy documents. MethodsPolitical economy and cultural safety lenses informed the study design. We analysed publicly-available documents for Australian population-wide food and nutrition policy consultations occurring 2008-2018. Data sources were policy documents, committee reports, terms of reference and consultation submissions. The submissions made by Aboriginal organisations were thematically analysed and key policy recommendations extracted. We examined the extent to which key recommendations made by Aboriginal organisations were included in the subsequent policy documents. ResultsFive food and nutrition policy processes received submissions from Aboriginal organisations. Key themes centred on self-determination, culturally-appropriate approaches to health, and the need to address food insecurity and social determinants of health. These messages were underrepresented in final policy documents, and Aboriginal people were not included in any committees overseeing policy development processes. ConclusionThis analysis suggests that very few Aboriginal organisations have participated in Australian population-wide food and nutrition policy processes and that these policy development processes are culturally unsafe. In order to operationalise First Nations peoples' right to self-determination, alternative mechanisms are required to redress the power imbalances preventing the full participation of Aboriginal and Torres Strait Islander peoples in population-wide food and nutrition policy decisions. This means reflecting on deeply embedded institutional structures and the normative assumptions upon which they rest.